Clinical characteristics and treatment outcomes for benign paroxysmal positional vertigo comorbid with hypertension. (4th May 2017) - Tan, Jun; Deng, Yuxiao; Zhang, Tianyu; Wang, Menghong
Abstract: Conclusions: Patients with BPPV comorbid with hypertension (h-BPPV) tend to receive a delayed diagnosis of BPPV. Comorbidity with hypertension did not influence the efficacy of the repositioning maneuver; however, comorbidity with hypertension was associated with an increased recurrence rate of BPPV. Objectives: To determine the clinical characteristics and outcomes of h-BPPV, as well as the clinical differences between h-BPPV and idiopathic BPPV (i-BPPV). Methods: The authors reviewed the medical records of 41 consecutive patients with h-BPPV (the h-BPPV group) from March to December 2014 and 47 patients with i-BPPV (the i-BPPV group) during the same period. Results: There were no significant differences in age, sex ratio, or the affected side between the h-BPPV and i-BPPV groups. The proportion of patients reporting an initial episode of positional vertigo was significantly lower in the h-BPPV group (51.22% vs 74.47%; p = .024). Patients in the h-BPPV group reported a longer median episode duration than did those in the i-BPPV group (60 days vs 15 days; p = .017). The results of treatment using repositioning maneuvers were similar between the two groups. At follow-up, 13 patients in the h-BPPV group were diagnosed with recurrent BPPV compared with six in the i-BPPV group ( p = .031).